Developing a Pop-Up Book to Enhance Indonesian Narrative Text Comprehension for Fourth-Grade Elementary School Students - Aida, Nun Asmi; Rahman, Alvin Yanuar; Saefuddin, Asis; Widowati, Kawuryansih (Journal of Integrated Elementary Education, 2025)
This study presents a comprehensive development of an interactive Pop-Up Book designed as an educational tool for Indonesian narrative texts, specifically tailored for fourth-grade students at the Islamic Elementary School of Bahrul Ihsan in Bandung City. Employing a rigorous Research and Development (R&D) methodology, the study utilized the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to ensure a systematic and empirical approach. Data was gathered through a variety of methods, including interviews with classroom teachers, validation questionnaires from media and material experts, and direct feedback from both the fourth-grade teacher and students following the media's implementation. The results indicate that the learning medium possesses high validity and practicality. Validation from experts was highly positive, with media experts assigning a remarkable rating of 99% and material experts rating it at 93%, both categorized as "Very Feasible." Similarly, evaluations from the implementing teacher and students were highly encouraging, with scores of 81% and 93% respectively, also classifying the medium as "Very Feasible." Therefore, this study demonstrates that the Pop-Up Book is an effective and engaging tool for enhancing student interest and promoting active learning. It successfully addresses the limitations of traditional, monotonous textbooks and aligns seamlessly with the pedagogical characteristics of Phase B students within the Merdeka Curriculum. This research makes a significant, evidence-based contribution to the advancement of innovative educational media for Indonesian language instruction.